CD4(+)CD25(hi)CD127(low) Regulatory T Cells Are Increased in Oral Squamous Cell Carcinoma Patients - Lim, K.P.; Chun, N.A.L.; Ismail, S.M.; Abraham, M.T.; Yusoff, M.N.; Zain, R.B.; Ngeow, Wei Cheong (Public Library of Science, 2014)
Regulatory T cells (Tregs), a subset of CD4+ T cells plays a pivotal role in regulating the immune system. An increase in Treg numbers enables cancer progression by dampening the immune system and allowing tumor cells to evade immune detection and destruction. An increase in Treg numbers and expression of inhibitory cytokines including TGF-β and IL-10 are mechanisms by which Tregs exert their immune suppressive function. However, the presence of Tregs and inhibitory cytokines in oral cancer patients is still unclear. In this study, the presence of circulating Tregs in 39 oral cancer patients and 24 healthy donors was examined by studying the presence of the CD4+CD25hiCD127low cell population in their peripheral blood mononuclear cells using flow cytometry. Serum levels of TGF-β and IL-10 were measured by ELISA. T cell subsets of OSCC patients were found to differ significantly from healthy donors where a decrease in CD8+ cytotoxic T cells and an increase in Tregs (CD4+CD25hiCD127low) were observed. Further, the ratio of CD8+ T cells/Tregs was also decreased in patients compared to healthy donors. The presence of Tregs was accompanied by a decrease in IL-10 but not TGF-β secretion in OSCC patients when compared to donors; in addition, the analysis also revealed that an increased presence of Tregs was accompanied by better patient survival. Amongst OSCC patients, smokers had significantly higher levels of TGF-β. It is apparent that the immune system is compromised in OSCC patients and the characterization of the Treg subpopulation could form a basis for improving our understanding of the perturbations in the immune system that occur during OSCC tumorigenesis.